Transport of arsenic loaded by ferric humate colloid in saturated porous media. (February 2020) - Yao, Youru; Mi, Na; He, Cheng; Yin, Li; Zhou, Dongbao; Zhang, Yong; Sun, Hongguang; Yang, Shaogui; Li, Shiyin; He, Huan
Abstract: The transport behavior of arsenic (As(V)) loaded by ferric humate (HA-Fe) colloid, denoted as HA-Fe/As(V), moving in a saturated quartz sand column, was tested in the laboratory under varying pH values, ionic strengths, and HA and Fe(III) content. The time-fractional advection-dispersion equation (fADE) model was then employed to analyze the observed migration of HA-Fe/As(V). Results showed that the stability of the HA-Fe colloid exhibited an upward trend with an increasing pH and HA content. An increasing HA content led to a decrease in the particle size of the HA-Fe colloid. However, the effect of Fe(III) concentration on colloidal particle size exhibited the opposite phenomenon. The ability of the HA-Fe colloid to load As(V) gradually increased with the increase of the Fe(III) concentration. During the co-transport of the HA-Fe/As(V) colloid, transport of As(V) was promoted with increasing pH, increasing HA and Fe(III) content, and decreasing ionic strength in the saturated porous medium. The transport behavior of As(V) can be well fitted by the fADE model. The model analysis revealed that sub-diffusion of As(V) was weakened in the HA-Fe/As(V) colloid with high HA content. Sub-diffusion of As(V) in the low pH colloid was stronger than that of the high-pH colloid, and the molecular diffusion and mechanical dispersion were more weakened in the high-pH colloid than that of the low-pH colloid. When observing varying ionic strengths, As(V) exhibited stronger sub-diffusion in the HA-Fe/As(V) colloid with a higher ionic strength. As for the Fe(III) content, transport of As(V) was mainly affected by sub-diffusion in the HA-Fe/As(V) colloid with a low Fe(III) content. These findings provided direct and necessary insights into the effects of the HA-Fe colloid on the migration of As(V) throughout saturated porous media under different hydrochemical conditions found in natural environments. Graphical abstract: Image 1 Highlights: With the Fe(III) concentration increased, more As(V) was bound by HA-FeS. During the co-transport of HA-Fe/As(V), transport of As(V) was promoted with pH, HA and Fe(III) increasing. The transport of As(V) can be fitted by the temporal fractional advection-dispersion equation model.